IDENTIFIKASI KANDUNGAN SENYAWA FITOKIMIA EKSTRAK ETANOL DAUN ASAM JAWA (TAMARINDUS INDICA L.) - Pahmi Husain; Dwi Kartika Risfianty; Khaerul Ihwan; Baiq Naili Dewi Atika; Irma Risvana Dewi; Muhammad Shohibul Ihsan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
Tamarind plant (Tamarindus indica L.) is one of the alternative plants that is widely used by the community in the medical and culinary fields. The utilization of tamarind leaves has been developed from generation to generation in traditional communities to urban areas until now. traditionally has medicinal properties. The content of tannin compounds, flavonoids, anthroquinone, saponins. Alkaloids contained in tamarind leaves can act as antibacterial. This study aims to identify the content of chemical compounds in tamarind leaves. The design of this study used a randomized block design. The research stages began with organoleptic testing of tamarind leaves, making extracts of young tamarind leaves and old tamarind leaves, then phytochemical screening tests (alkaloid test, flavonoid test, saponin test, tannin test, and steroid/triterpenoid test) and and continued with antibacterial activity test. The results showed that young tamarind leaves did not contain alkaloids and saponins, while old tamarind leaves contained flavonoids, alkaloids, tannins, and steroids/terpenoids. The antibacterial activity of young tamarind leaves was higher than that of old tamarind leaf extract. Keywords : Phytochemical Compounds, Ethanol, Tamarind, Randomized Block Design